Facilitated gate setting by sequential dot plot scanning. (9th March 2015) - Günther, Susanne; Müller, Susann; Brinkman, Ryan R.; Aghaeepour, Nima; Finak, Greg; Gottardo, Raphael; Mosmann, Tim; Scheuermann, Richard H.
Abstract Microbial communities comprising thousands of unknown organisms can be studied flow cytometrically by applying just one fluorescent parameter and using scatter characteristics of cells. Resulting 2D‐plots need to represent high numbers of cells to detect the many subcommunities, even rare ones that might be present in the sample. Evaluation of such data can be faulty and subjective due to the low number of parameters available for data discrimination and the high numbers of overlaying events. Here, we describe a procedure that helps to evaluate such data using facilitated gate setting by sequential dot‐plot scanning. © 2015 International Society for Advancement of Cytometry